Case Report: Metagenomics Next-Generation Sequencing Can Help Define the Best Therapeutic Strategy for Brain Abscesses Caused by Oral Pathogens - Ma, Zhonghui; Yan, Su; Dong, Haoxin; Wang, Huifen; Luo, Yonggang; Wang, Xi (Frontiers in Medicine, 2021)
Brain abscesses are associated with an increased long-term risk of new seizures and increased mortality within several years after infection. Common microorganisms that cause brain abscesses include bacteria, fungi, and mycoplasma. We report a 75-year-old man with a brain abscess caused by Prevotella denticola, an oral pathogen. Based on the clinical condition, we suspected that the patient had a blood-borne brain abscess, and he received antibiotics and systemic supportive treatment. The patient developed shock for the second time after negative Gram-staining results. Metagenomics next-generation sequencing showed one strain from the oral microbiome, confirming our hypothesis, and targeted antibiotic treatment was administered quickly. Thus, we report a case in which genomic analysis was the critical factor in determining the best antimicrobial therapy for administration.